2021
DOI: 10.1101/2021.07.16.452533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation cues in nucleosome geometry, stability, and unwrapping

Abstract: Cytosine methylation at the 5-carbon position is an essential DNA epigenetic mark in many eukaryotic organisms. Although countless structural and functional studies of cytosine methylation have been reported in both prokaryotes and eukaryotes, our understanding of how it influences the nucleosome assembly, structure, and dynamics remains obscure. Here we investigated the effects of cytosine methylation at CpG sites on nucleosome dynamics and stability. By applying long molecular dynamics simulations (five micr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 61 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…First, as shown in Figures 1d and 1f, in both canonical and variant systems one DNA end unwraps, while another end stays more bound to a histone octamer. Indeed, previous single-molecule FRET experiments and MD simulations have demonstrated that the DNA unwrapping occurred asymmetrically and DNA unwrapping at one side stabilized the DNA end on the other side (29)(30)(31). Moreover, we observe the difference in terms of the degree of unwrapping for both DNA ends that can be related to the asymmetry of our nucleosomal DNA sequence with respect to the dyad position.…”
Section: H2az Deposition Facilitates the Dna Unwrappingsupporting
confidence: 54%
See 2 more Smart Citations
“…First, as shown in Figures 1d and 1f, in both canonical and variant systems one DNA end unwraps, while another end stays more bound to a histone octamer. Indeed, previous single-molecule FRET experiments and MD simulations have demonstrated that the DNA unwrapping occurred asymmetrically and DNA unwrapping at one side stabilized the DNA end on the other side (29)(30)(31). Moreover, we observe the difference in terms of the degree of unwrapping for both DNA ends that can be related to the asymmetry of our nucleosomal DNA sequence with respect to the dyad position.…”
Section: H2az Deposition Facilitates the Dna Unwrappingsupporting
confidence: 54%
“…In the first section, we showed that DNA ends of H2A.Z-containing nucleosomes are more mobile and are easier to unwrap from the histone octamer when compared to nucleosomes containing canonical H2A. It has been reported earlier that H3 N-terminal and H2A C-terminal tails mediated the unwrapping of DNA ends in nucleosomes (30,31,37-41). Consistent with these findings, we show that the degree of DNA unwrapping is anti-correlated with the number of contacts between the H2A.Z C-terminal tail and the outer DNA region (Figure 2a, see Supplementary Figure S5 for definitions of DNA regions).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…1b, c, in both canonical and variant systems one DNA end unwraps, while another end stays bound to a histone octamer. Previous single-molecule FRET experiments and MD simulations demonstrated that DNA unwrapping indeed occurred asymmetrically and DNA unwrapping at one side stabilized the DNA end on the other side [31][32][33] . Moreover, we observe the difference in terms of the degree of unwrapping for both DNA ends that can be related to the asymmetry of our nucleosomal DNA sequence with respect to the dyad position.…”
Section: H2az Deposition Facilitates the Dna Unwrappingmentioning
confidence: 97%
“…For example, acetylation could neutralize the positive charges on histone tails to weaken their binding with DNA, [34][35][36][37] while methylation may lead to under-twisted DNA that strengthens its interactions with histones. 38,39 It's conceivable that nucleosomes with similar histone marks share more favorable interactions, driving their separation from other differentially modified ones. On the other hand, chromatin regulators associated with specific histone marks often contain intrinsically disordered regions that exhibit multivalent interactions to undergo liquid-liquid phase separation themselves.…”
Section: Introductionmentioning
confidence: 99%